2011
DOI: 10.4174/jkss.2011.81.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of radiofrequency ablation and surgical resection for colorectal liver metastases

Abstract: PurposeTo evaluate the comparative therapeutic efficacy of radiofrequency ablation (RFA) and hepatic resection for the treatment of colorectal liver metastasis (CRLM).MethodsBetween 1996 and 2008, 177 patients underwent RFA, 278 underwent hepatic resection and 27 underwent combination therapy for CRLM. Comparative analysis of clinical outcomes was performed including number of liver metastases, tumor size, and time of CRLM.ResultsBased on multivariate analysis, overall survival (OS) correlated with the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(105 citation statements)
references
References 30 publications
(41 reference statements)
3
97
0
5
Order By: Relevance
“…Some centres treat up to nine tumours, if the maximum diameter is <4 cm, and usually at two treatment sessions [48,49]. As in the resection literature, the best results are achieved in solitary tumours, Gillams et al [32] reported 3-year survival in excess of 80 % and Kim et al [50] reported 5-year survival of 51 % in solitary tumours. Additional tumours that develop during follow-up, including new tumours in the postresection liver remnant or local recurrence, should be considered for ablation based upon anatomical and size criteria.…”
Section: Tumour Numbermentioning
confidence: 99%
“…Some centres treat up to nine tumours, if the maximum diameter is <4 cm, and usually at two treatment sessions [48,49]. As in the resection literature, the best results are achieved in solitary tumours, Gillams et al [32] reported 3-year survival in excess of 80 % and Kim et al [50] reported 5-year survival of 51 % in solitary tumours. Additional tumours that develop during follow-up, including new tumours in the postresection liver remnant or local recurrence, should be considered for ablation based upon anatomical and size criteria.…”
Section: Tumour Numbermentioning
confidence: 99%
“…Neuere Arbeiten legen die Vermutung nahe, dass bei solitären Lebermetastasen < 3 cm mittels RFA ähnlich gute Ergebnisse wie durch die Resektion erzielt werden können [712,713]. Die bisherige Datenlage hierzu ist aber widersprüchlich und es fehlen weiterhin vergleichende kontrollierte-randomisierte Studien.…”
Section: Level Of Evidence 3aunclassified
“…Hence, RFA can be recommended as an alternative treatment for patients who are not candidates for surgery. Kim et al [20] claim that RFA is a safe alternative treatment for solitary colorectal liver metastases <3 cm, with outcomes equivalent to those achieved with HR. Furthermore, Gillams et al [21] report that RFA for solitary liver metastases ≤4 cm can be performed with minimal morbidity and results in excellent long-term survival, approaching that of surgical resection, even in patients who are not candidates for surgery.…”
Section: Discussionmentioning
confidence: 99%